Vehicle Load Effect of Long-Span Bridges: Assessment with Cellular Automaton Traffic Model. Issue 1 (January 2015) - Wu, Jun; Yang, Fei; Han, Wanshui; Wu, Liujie; Xiao, Qiang; Li, Yanwei
Vehicle load is one of the primary live loads for long-span bridges. However, load distribution and composition are complicated on long-span bridges and vary significantly. In general, bridge codes do not include specifications for bridges with long spans. In this study, the microscale traffic model, cellular automaton (CA) model, was adopted to establish a long-span vehicle load model through a merger with real-monitored traffic data. The differences in the current design vehicle loads used in China, the United States, Great Britain, and Europe are discussed. The effects of the CA load with different vehicle density and vehicle composition were estimated for loaded lengths from 100 to 1, 000 m with the influence line. The largest moment of a bridge from a CA load was compared with that of the design vehicle load statistically. The results showed that vehicle density, loaded length, and the heavy truck percentage were the main features of the vehicle loading effects. An increase in vehicle density led to higher average and extreme values for the loading effect. When the loaded length was more than 600 m, the impact of the loaded lengths vanished. When the vehicle density was the same, a heavy percentage of truck traffic had a significant impact on the loading effect. Moreover, when the percentage of heavy trucks was high, the design load for relatively shorter loaded lengths needed to be adjusted because the current design load safety margin for a loaded length of not more than 300 m was small.